Agronomic performance of peach trees grown in subtropical region - Segantini, Daniela Mota [UNESP]; Leonel, Sarita [UNESP]; Silva, Adriana de Castro Correia da; Ferraz, Rafael Augusto [UNESP]; Ripardo, Ana Karolina da Silva [UNESP] (Scientific Research Publishing, 2014)
Peach trees are temperate climate fruit trees most planted in subtropical and tropical regions. This advance of the peach crop is mainly due to the introduction of less cold-demanding new cultivar varieties and which require using less specific techniques, such as plant growth regulators and pruning. Within this context, the objective of this work was to evaluate phenological aspects and the yield potential of the cultivars Granada, Aurora-1, Dourado-2, Douradao, Big-Aurora, Marli and Chiripá, grafted onto the “Okinawa” rootstock, planted in the region of Sao Manuel-SP, during two cultivation cycles. The experimental design used was a completely randomized design with 7 treatments and 5 replicates, with the experimental unit represented by two plants.”Granada” had early harvest in mid-September, and “Chiripá” in late November and early December, in which the former was the early-ripening cultivar and the latter was the late-ripening one. “Aurora-1” and “Dourado-2”, had the highest yield values, 18.95 and 16.57 t∙ha−1 respectively, followed by “BigAurora” with yield values of 12.13 t∙ha−1. For subtropical regions, such as São Manuel-SP, less colddemanding cultivars are recommended, such as Aurora-1, Dourado-2 and Big-Aurora. The planting of early- and late-ripening varieties, such as Granada and Chiripá, respectively, is an interesting alternative for producers wanting to scale their production.
Keywords: Phenology; Production; Buds; Cultivars; Prunuspersica